2016
DOI: 10.1021/acs.iecr.6b00804
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Performance of NO Reduction by CO over Activated Semicoke Supported Fe/Co Catalysts

Abstract: Performance of NO reduction by CO is studied over activated semicoke supported Fe/Co catalysts (FeCo/ASC). The influence of oxygen and CO concentration is investigated systematically. It is found that excess CO, with a CO:NO ratio greater than 2:1, could significantly enhance NO reduction, but oxygen, even with a concentration less than 1%, could strongly inhibit NO conversion efficiency due to the oxidation of active surface metal sites. To explore the role of CO in NO reduction, reactions without CO addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…The reaction of C(O) with an oxidized metal site (*O) that formed CO 2 and activated the metal site (*) can be used later for the reduction of NO to N 2 O or N 2 . The mechanism can be expressed as the following reactions [56]:…”
Section: Catalytic Activity Evaluationmentioning
confidence: 99%
“…The reaction of C(O) with an oxidized metal site (*O) that formed CO 2 and activated the metal site (*) can be used later for the reduction of NO to N 2 O or N 2 . The mechanism can be expressed as the following reactions [56]:…”
Section: Catalytic Activity Evaluationmentioning
confidence: 99%
“…On the other hand, the peak area of SO 2 increases with increasing O 2 volume fraction of the carrier gas from 5 to 10% since increasing O 2 favors SO 2 formation. However, the SO 2 peak area shows a slight declining trend in the combustion stage when O 2 increases from 10 to 21% because abundant O 2 also facilitates SO 2 capture through Reaction (7).…”
Section: Effect Of Atmosphere On the Gas Evolvedmentioning
confidence: 99%
“…Secondly, the O 2 concentration of the mix gas can be adjusted below the 21% of air, which slows down the oxidation of shale oil. The third reason is that CO 2 in ambient gas generates a reductive atmosphere and thus reduces NOx emission [7]. And, last, the ambient gas containing a high concentration of CO 2 could promote the sulphuration of KCl in wheat straw semicoke and alleviate the high-temperature corrosion [8].…”
Section: Introductionmentioning
confidence: 99%
“…14 Carbonbased materials can also be used as supports for NO x reduction by CO at low temperature (below 300 1C). 15 Yao et al 16 used Ce 0.67 Sn 0.33 O 2 , Ce 0.67 Zr 0.33 O 2 , and Ce 0.67 Ti 0.33 O 2 as supports for the preparation of copper-based catalysts for the NO + CO reaction. They found that CuO/Ce 0.67 Zr 0.33 O 2 was reduced more easily than other catalysts, most probably due to the differences in the electronegativity of the dopant.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic performance of Fe/Co catalyst over activated semicoke (ASC) for NO reduction by CO was investigated. 7,15 The catalyst revealed excellent performance under oxygen-free conditions, but due to the oxidation of active metal sites in the presence of oxygen, the NO + CO reaction was strongly inhibited; CO will be quickly consumed, and oxygen preferentially oxidizes CO over the carbon support; then, NO-carbon reaction will be the main reaction. Formation of surface oxygen compounds in the presence of oxygen could enhance the NO-carbon reaction.…”
Section: Introductionmentioning
confidence: 99%